2010
DOI: 10.1242/jcs.058321
|View full text |Cite
|
Sign up to set email alerts
|

The heparin-binding domain of HB-EGF mediates localization to sites of cell-cell contact and prevents HB-EGF proteolytic release

Abstract: SummaryHeparin-binding EGF-like growth factor (HB-EGF) is a ligand for EGF receptor (EGFR) and possesses the ability to signal in juxtacrine, autocrine and/or paracrine mode, with these alternatives being governed by the degree of proteolytic release of the ligand. Although the spatial range of diffusion of released HB-EGF is restricted by binding heparan-sulfate proteoglycans (HSPGs) in the extracellular matrix and/or cellular glycocalyx, ascertaining mechanisms governing non-released HB-EGF localization is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 76 publications
0
35
0
Order By: Relevance
“…Sulfated polysaccharides present within the ECM play a determining role in cell fate by regulating ligand binding to transmembrane receptors. For example, heparan sulfate, a sulfated ECM glycosaminoglycan, regulates the diffusion of the ligand of the epidermal growth factor (EGF) receptor through the ECM by mediating its sequestration by proteoglycans (Prince et al, 2010). This sequestration engages the cell in growth inhibition instead of cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfated polysaccharides present within the ECM play a determining role in cell fate by regulating ligand binding to transmembrane receptors. For example, heparan sulfate, a sulfated ECM glycosaminoglycan, regulates the diffusion of the ligand of the epidermal growth factor (EGF) receptor through the ECM by mediating its sequestration by proteoglycans (Prince et al, 2010). This sequestration engages the cell in growth inhibition instead of cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, application of heparin-binding epidermal growth factor-like growth factor (HB-EGF)-which is known to be upregulated both in human burn tissue and during healing of partial-thickness burn injuries specifically through potentiation of the expression of transforming growth factor-a, another member of the EGF family of growth factors involved in wound repair (Cribbs et al, 1998)-can promote healing of ileal tissue 120 after experimental reanastomosis surgery (Radulescu et al, 2011). Localization of HB-EGF through binding to HSPG facilitates juxtacrine inhibition of cell proliferation by this growth factor, and disruption of this binding allows the released HB-EGF to function as an autocrine mitogen (Prince et al, 2010). Therefore, it is possible that soluble heparin at the site of injury could act competitively to release this growth factor from HS binding sites and promote participation in tissue repair.…”
Section: Would Healing and Tissue Repairmentioning
confidence: 99%
“…Studies in vitro showed that a TGF-a proprotein carrying mutations in the metalloproteinase cleavage site could signal, but in vivo, mutation of the metalloproteinase itself appeared to recapitulate loss of TGF-a (Brachmann et al, 1989;Peschon et al, 1998;Sanderson et al, 2006;Wong et al, 1989). In recent years, mounting evidence has been provided in support of pro-protein signaling, both by TGF-a and by HB-EGF, which has opposing effects on cell survival in its membrane-bound and secreted forms (Pan et al, 2002;Prince et al, 2010;Shi et al, 2000;Singh et al, 2007;Yang et al, 2000). Some pro-proteins, such as amphiregulin, might be released on exosomes, allowing them to act at a distance (Higginbotham et al, 2011).…”
Section: Pro-protein Signalingmentioning
confidence: 99%
“…Mammalian EGFR ligands have also been observed to induce juxtacrine pathway activation by binding to their receptors in their transmembrane pro-protein forms (Anklesaria et al, 1990;Brachmann et al, 1989;Wong et al, 1989). Juxtacrine and paracrine activation of the receptor can result in different outcomes, suggesting that regulation of ligand cleavage can determine the consequences of pathway activity (Iwamoto et al, 1999;Pan et al, 2002;Prince et al, 2010;Singh et al, 2004;Takemura et al, 1997).…”
Section: Introductionmentioning
confidence: 99%